PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY - Sulu, Rudi Bida; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2023)
This research was conducted because there was no specific method for managing raw material inventory at YY Kebab which resulted in high ordering costs due to the ordering frequency being too high and raw materials not being used optimally. This research uses the EOQ (Economic Order Quantity) method which will provide an overview of the optimal order quantity, optimal purchase frequency, safety stock and re-order point. The aim of this research is to know raw material inventory control processes with actual conditions and the influence of Economic Order Quantity method implementation on the total of raw materials inventory costs at YY Kebab. Data collection was carried out using observation and interview techniques, while the data analysis method used was the Economic Order Quantity method taking into account TIC (Total Inventory Cost), safety stock, reorder frequency, and ROP (Re-Order Point). The research results show that using the Economic Order Quantity method can reduce total inventory costs by a specific amount when compared to the actual method.